Strategy for Increasing Customer Financial Literacy on Decisions to Use Financial Products, Especially Savings Products at PT BPD Sumsel Babel Muaradua Branch Office - Lillah Mau'izzah; Bagus Panuntun (Publikasi Inspirasi Indonesia, 2024)
This study aims to analyze the strategy of improving customer financial literacy on the decision to use savings financial products of PT BPD Sumsel Babel Muaradua Branch Office. PT BPD Sumsel Babel is one of the leading financial institutions in Indonesia whose main objective is to support economic growth in South Sumatra and Bangka Belitung. This research is quantitative descriptive with the methods used are library research, direct observation in the field and documentation. Participant selection technique through purposive sampling model with target questionnaire that is customer. The number of respondents was 255 customers. The questionnaire in this study was processed through the Microsoft Excel application. The expected outcome of this research is the preparation of effective strategies in improving customer financial literacy and the implementation of literacy programs that can have a positive impact on customers. Policy recommendations for Bank Sumsel Babel Muaradua Branch Office involve providing ongoing financial literacy programs, improving educational communications, personal financial counseling services, developing financial literacy applications, and incentives for active customers. Enabling factors include management support, active customer participation, and availability of resources.